Ultrasonography evaluation of small bowel bezoars with suspicious findings on CT in the elderly (Annals of Medical Research, 2021)
Aim: Our aim was to evaluate the feasibility of using ultrasonography (US) in the detection and management of small bowel bezoars in elderly patients (> 65 y).Material and Methods: This study included 15 elderly patients (> 65 y) with small bowel obstruction and initial diagnosis of small bowel bezoar using abdominal computed tomography (CT) from among 182 patients with small bowel obstruction. The diagnostic performance of US was prospectively evaluated and compared with the surgical or clinical diagnoses.Results: Among the 15 patients, ten of them were diagnosed via ultrasonography as having small bowel bezoar. Eight patients were also surgically diagnosed with phytobezoars, and the remaining two patients who showed bezoars on US showed complete symptomatic improvement with ultrasonographic follow-up showing the bezoar passing through the cecum. The other five patients were surgically diagnosed with brid ileus. US correctly diagnosed small bowel bezoars in all patients. The sonographic follow-up of the bezoars in the two patients who showed symptomatic improvement was also successful.Conclusion: US is a feasible imaging modality for the diagnosis and follow-up of small bowel bezoars. Timely diagnosis and management of bezoars is especially important in elderly patients. US can help both, radiologists and clinicians in easy diagnosis and timely management of small bowel bezoars in elderly patients.Keywords: Bezoar; phytobezoar; ultrasonography; computed tomography; elderly.
Keywords: Bezoar; phytobezoar; ultrasonography; computed tomography; elderly.